A Quantitative Study Exploring Motivation, Anxiety, and Enjoyment in Learning English Among Pakistani Undergraduates - Farhad, Ullah (Unversity Malaysia Sarawak, 2025)
This study explores the interrelationship between motivation, anxiety, and enjoyment among undergraduate English as a Second Language (ESL) learners in public universities in Khyber Pakhtunkhwa (KPK), Pakistan. This research employs Gardner’s Socio-Educational Model (SEM), Horwitz, Horwitz, and Cope’s Foreign Language Anxiety (FLA) theory, and the Positive Psychology theory to investigate the levels of these factors, their correlations, and the impact of demographic characteristics, including university, age, gender, academic major, and parental education. The study utilizes a quantitative approach, collecting data through a survey administered to 381 ESL undergraduates from three different universities. Findings revealed high motivation levels among students (M = 3.88, SD = 0.96), particularly in components such as desire (M = 3.92) and intensity (M = 3.89), with a stronger inclination toward productive skills (speaking and writing) over receptive ones. Anxiety levels were moderate (M = 3.11, SD = 1.25), with speaking and listening anxiety being more pronounced than other domains. Enjoyment was generally high (M = 3.73, SD = 1.08), especially in subdomains of creativity (M = 3.85) and positive classroom environment (M = 3.80). Statistical analysis indicated significant negative correlations between anxiety and both motivation (r = –0.43, p < 0.01) and enjoyment (r = –0.48, p < 0.01), while motivation and enjoyment were positively correlated (r = 0.55, p < 0.01). Demographic variables showed varied influences; for example, females reported higher anxiety (p = 0.035), while learners with postgraduate-educated mothers showed significantly higher motivation and enjoyment and lower anxiety (p < 0.01). The research highlights the critical role of emotional factors in ESL learning and provides practical implications for educators and policymakers to enhance the effectiveness of English language instruction in the text. The study underscores the importance of creating a supportive learning environment that fosters motivation and enjoyment while mitigating anxiety to improve language acquisition outcomes. Keywords: Motivation, anxiety, enjoyment, undergraduate learner, ESL